Correlações entre as variáveis de frequência de treinamento, antropométricas, educacionais, socioeconômicas, imagem corporal e o consumo de macro e micronutrientes em jogadoras de futsal - RODRIGUES, Fabiana Viana Maciel (2022)
Objective: Identify and correlate training frequency, anthropometric, educational, socioeconomic variables, nutritional status, body image and macro and micronutrient consumption in indoor soccer players. Materials and methods: Twenty-two adult female futsal players were evaluated, where the procedures for Assessment of training volume, in training time in years, training time in weekdays and training time in hours per day were carried out; Self-reported anthropometric assessment of weight and height; Classification of the Body Mass Index; Identification of the level of education; Socioeconomic classification through the questionnaire of the Brazilian Association of Research Companies; Body image assessment using the Body Shape Questionnaire and Stunkard's silhouette scale; Food consumption assessment using the Food Diary tool with a duration of 4 non consecutive days. All questionnaires were adapted and sent online via Google Forms. Results: The mean age was 27.64 ±4.85 years; average weight of 69.92 ±10kg, average height of 1.61 ±0.06m. 9.09% were Thin, 59.09% were Eutrophic, 22.72% were Overweight, 9.09% were Obesity I grade. 45.45% perform two weekly training sessions, and 31.81% perform three weekly training sessions, 4.54% reported training six times a week. 54.54% reported training for at least more than two hours and less than three hours a day. 31.82% reported training for at least more than an hour and less than two hours a day, 4.54% reported training for more than three hours a day. As for education, 18.18% reported having completed high school, 4.54% reported not completing high school, 31.81% having completed higher education, 36.36% reported having incomplete higher education. As for socioeconomic stratification, 9.09% were in economic class C2, 31.81% were in economic class C1, 36.36% were in economic class B2, 13.63% were in economic class B1, 4.54% were in socioeconomic stratum A. Regarding body image, 18.18% were satisfied. However, 68.18% were dissatisfied with their excess weight and 13.63% were dissatisfied with being thin. 95.45% had no body dissatisfaction and 4.54% had mild body dissatisfaction. As for caloric consumption, analyzed on Sunday, the average caloric consumption was 1,854 ±744.91kcal, the average protein consumption was 91.20 ±36.29, equivalent to 21.10% of the total energy value. . The average found for carbohydrates was 201.05 ± 89.54g, equivalent to 43.87% of the total energy value (VET). The average amount of lipids was 74.04 ±41.18g, equivalent to 35.02% of the VET.Conclusion: Futsal players had insufficient training volume at a high performance level. And most of the players were classified as eutrophic, on the other hand, they were dissatisfied with their self-perception of body image. As for food consumption, they had low consumption of carbohydrates, moderate consumption of proteins and a high consumption of lipids, as well as inadequacies in the consumption of micronutrients.